Simulação de evacuação de multidão por autômato celular - Estudo de caso em um estádio de futebol - Carneiro, Lílian de Oliveira (2012)
The evacuation from crowded places, subjected to physical and temporal restrictions, is a matter that deserves special attention. If a crowd fails to escape in time from a hazardous environment, by taking a wrong way or by selecting a bad exit, there is great risk of injuries and death. Simulations of crowd evacuation are very important to try to minimize those types of risk. However, trying to simulate emergency situations in real environments is either very expensive or even impossible. Therefore, computer simulation of crowd evacuation is a better alternative. The soccer stadiums are examples of environments that may present risk to people's lives in case of emergency evacuation. The main objective of this work is to gain understanding of the inherent aspects of the problem of emergency evacuation simulation, and to investigate the dynamics of the evacuation behavior of crowds during an emergency evacuation from a soccer stadium. For this, it was proposed a new model for crowd evacuation based on the cellular automata model. In order to validate the proposed model, tests in different situations were performed. It was shown that the proposed model is able to simulate the evacuation of complex environments in an efficient way.